2021
DOI: 10.1111/tid.13627
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the association between cytomegalovirus DNAemia and subsequent acute graft‐versus‐host disease in allogeneic peripheral blood stem cell transplantation: A multicenter study from the Spanish hematopoietic transplantation and cell therapy group

Abstract: The potential role of active CMV infection in promoting acute Graft-versus-Host Disease (aGvHD) in allogeneic hematopoietic stem cell transplantation (allo-HSCT) remains a matter of debate. We further addressed this issue conducting a retrospective, observational, multicenter study of 632 patients subjected to allogeneic pe-How to cite this article: Bueno F, Solano C, Vázquez L, et al. Assessment of the association between cytomegalovirusDNAemia and subsequent acute graft-versus-host disease in allogeneic peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In turn, a large number of nonessential CMV genes (around one‐third of the CMV genome) encode proteins with proinflammatory (human homologs of cytokines, chemokines, or chemokine receptors) or immunosuppressive (i.e., inhibitors of natural killer [NK]‐cell activation or antigen presentation to CD4 + and CD8 + T cells) properties 4,5 . The proinflammatory and immunosuppressive nature of CMV mechanistically supports the association reported in some series between CMV infection and the occurrence of acute graft versus host disease (aGvHD) or virus superinfections (i.e., due to Epstein–Barr virus), 7,8 both among the so‐called “indirect effects.” Moreover, CMV DNAemia was suggested to be associated in a positive dose–response manner with an increased risk of overall mortality (OM) and nonrelapse mortality (NRM) in the first year after allo‐SCT, independent of the use of PET 9 . The link between CMV DNAemia, most notably that requiring PET, and OM/NRM has also been observed in other studies, 10,11 including a meta‐analysis and meta‐regression analysis 12 .…”
Section: Clinical Relevance Of CMV Infection In the Allo‐sct Settingmentioning
confidence: 63%
“…In turn, a large number of nonessential CMV genes (around one‐third of the CMV genome) encode proteins with proinflammatory (human homologs of cytokines, chemokines, or chemokine receptors) or immunosuppressive (i.e., inhibitors of natural killer [NK]‐cell activation or antigen presentation to CD4 + and CD8 + T cells) properties 4,5 . The proinflammatory and immunosuppressive nature of CMV mechanistically supports the association reported in some series between CMV infection and the occurrence of acute graft versus host disease (aGvHD) or virus superinfections (i.e., due to Epstein–Barr virus), 7,8 both among the so‐called “indirect effects.” Moreover, CMV DNAemia was suggested to be associated in a positive dose–response manner with an increased risk of overall mortality (OM) and nonrelapse mortality (NRM) in the first year after allo‐SCT, independent of the use of PET 9 . The link between CMV DNAemia, most notably that requiring PET, and OM/NRM has also been observed in other studies, 10,11 including a meta‐analysis and meta‐regression analysis 12 .…”
Section: Clinical Relevance Of CMV Infection In the Allo‐sct Settingmentioning
confidence: 63%
“…Several studies have reported either a higher incidence of CMV DNAemia 4–9 or faster plasma CMV DNA duplication times 10 in PT/Cy‐haplo compared to HLA‐matched allo‐HSCT; nevertheless, these observations could not be explained by differences in the kinetics of CMV‐specific T‐cell reconstitution early after allo‐SCT 11 . The impact of the overall degree of HLA class I and II mismatching on the frequency of CMV DNAemia has been documented in cord blood transplantation, 30 in which setting a significant effect on the incidence of CMV reactivation was noted for HLA disparity (HR: 0.54 for 8/8 match compared with 3‐allele mismatch).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Several studies have shown that Cytomegalovirus (CMV) DNAemia occurs at an exceedingly high frequency in PT/Cy-haplo compared to other allo-SCT modalities. [4][5][6][7][8][9] Moreover, subtle dissimilarities between PT/Cy-haplo and human leukocyte antigen (HLA)-matched allotransplants have been reported, namely shorter CMV DNA doubling times in plasma and higher CMV DNA peak levels in the former. 10,11 Robust reconstitution of functional CMV-specific CD8 + T cells has been shown to contribute crucially in preventing and resolving CMV DNAemia episodes in the allo-SCT setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 80% of CMV seropositive recipients can experience viral reactivation after allo-HSCT during the T-cell depletion phase. [3][4][5][6][7] CMV reactivation is reported to be associated with an increased risk for secondary bacterial and fungal infections, tissue-invasive CMV illness if neglected, 8 as well as graft-versus-host-disease (GvHD), [9][10][11] and increases mortality rates. 12 Pre-emptive therapy (PET) has been found to significantly lower the incidence of CMV infection in those who have undergone an HSCT.…”
Section: Introductionmentioning
confidence: 99%